DETERMINANTS OF THE BALANCE OF PAYMENTS IN INDONESIA: A SHARIA ECONOMIC PERSPECTIVE - Tubagus Iqbal Fajar; Dimas Pratomo; Citra Etika (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2025)
This study aims to analyze the influence of foreign direct investment, inflation, and the difference between exports and imports on Indonesia's balance of payments, specifically for the period 2015-2024, both partially and simultaneously, using a sharia economic perspective. This study employed descriptive quantitative research. The data analysis method used was multiple regression analysis. The results of this study indicate that foreign direct investment (FDI) has a partial effect on Indonesia's balance of payments. Increasing FDI flows into Indonesia can make a positive contribution through additional foreign capital, increased production capacity, and job creation, which supports international trade performance. Exports have a partial effect on Indonesia's balance of payments. High export values ​​can provide a positive signal regarding the fundamental condition of the Indonesian economy. Imports have a partial effect on Indonesia's balance of payments. Increased imports contribute positively, especially if the imports are in the form of capital goods, technology, or raw materials. The inflation rate affects Indonesia's balance of payments. Increased inflation has a significant effect on the balance of payments.